… but what about the Aboriginal and/or Torres Strait Islander Health Worker academic? Transcending the role of ‘unknowing assistant’ in health care and research through higher education: a personal journey - Stajic, Janet (The Australian Journal of Indigenous Education, 2020)
Abstract The Aboriginal and Torres Strait Islander Health Worker/Practitioner (A&TSIHW) workforce provides not only clinical skills but also responds to specific social and cultural needs of the communities they serve bringing knowledge derived from lived and embodied knowledges. The A&TSIHW is a recognised health professional within the Australian health system; however, this workforce continues to be under-supported, under-recognised and under-utilised. A common discourse in literature written about A&TSIHWs focused on the need to empower and enhance the A&TSIHW capabilities, or rendered the A&TSIHW as part of the problem in improving the health of Indigenous peoples. In contrast, articles written by A&TSIHWs, published in the Aboriginal and Islander Health Worker Journal, tell a different story, one about the limitations of the health system in its ability to care for Indigenous peoples, recognising A&TSIHW leadership. This paper deals with two interrelated tensions—the undervaluing of the A&TSIHW as a clinician and the undervaluing of the A&TSIHW as an academic—both of which the author has had to navigate. It explores the specific challenges of the A&TSIHW academic who too seeks recognition beyond that of ‘assistant’ within the research enterprise, drawing upon personal experiences and engagement with educational institutions, including higher education.